Cysteine proteinase inhibitors stefin A and stefin B in operable carcinoma of the head and neck - Strojan, Primož (Radiology and oncology (Ljubljana), 2002)
Purpose. To evaluate the significance of cysteine proteinase inhibitors stefins (Stefs) A and B for a treatment decision and prognosis in operable squamous cell carcinoma of the head and neck (SCCHN). Patients and methods. Stefs A and B concentrations were determined immunobiochemically using ELISAs in cytosols prepared from the tumor and adjacent normal mucosa from 91 patients with operable SCCHN. The median follow-up period of patients alive atthe close-out date was 5.8 years (range, 5-9.3 years). Results. Stef A concentrations were significantly higher in tumor compared to normal mucosa (FM.05). When a subgroup with clinically palpable nodes) at presentation was taken into consideration (n=57), a significant difference in Stef A (P=0.03) and Stef B (P=0.02) concentrations between those with negative and positive necks, as determined on histopathological examination, was observed. On the univariate survival analysis, higher Stefsć concentrations turned to be prognostically advantageous. Stef A proved its independent prognostic significance also on multivariate setting. Conclusions. With the capability todifferentiate between the pN0- and pN+-stages of the disease in the patientsoriginally presented as node-positive, Stefs A and B could be useful markers when deciding on the extent of neck surgery. In addition, both Stefs proved to be reliable prognosticators for survival in patients with operable SCCHN.
Keywords: cisteinske proteinaze; glava; novotvorbe; rak (medicina); tumor; vrat; Vrata